Alternative Approaches for Rating INDCs: a Comparative Analysis - Marinella Davide; Paola Vesco (Fondazione Eni Enrico Mattei (FEEM), 2016)
The “Intended nationally determined contributions” (INDCs) communicated by both developing and developed countries represent a crucial element of the Paris agreement. This paper aims at analysing the INDCs submitted by Parties, through the different tools and approaches proposed by the research community. In particular, our analysis looks at the different ways to assess the effectiveness of the proposed emission reduction pledges, both in terms of aggregate and national efforts. However, we also consider other factors that will be critical in determining the success of the Paris talks, such as the coherence and fairness of single contributions.
Keywords: F50; F51; F53; K33; 330; Paris Agreement; INDCs; Mitigation; Ambition; Efficiency; Equity; Carbon Budget